Analisis Efektivitas Transformasi Digital Marketing Berbasis Software as a Service (SaaS) terhadap Daya Saing Visual UMKM Desa Bandar Kumbul - Rinda Puspita; Budianto Bangun; Rahma Muti Ah; Syaiful Zuhri Harahap (Universitas Labuhanbatu, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the economy, but they still face challenges in promotion, particularly in utilizing digital media. MSMEs in Bandar Kumbul Village generally still use traditional methods and are unable to create engaging promotional content. This activity aims to improve MSMEs' understanding and skills in using the Canva application as a digital promotional tool. The method used is community service through preparation, implementation, and evaluation stages using the 70/20/10 learning model. Data was collected through observation, interviews, and pre- and post-tests. The results show an increase in participants' knowledge and skills in creating promotional content such as posters, banners, and social media, as well as an increase in digital media utilization and understanding of branding. Therefore, Canva is effective in improving the quality of promotions, expanding market reach, and enhancing the competitiveness of MSMEs.